Expression of 34β E 12 in prostatic lesion - Dr. L. Arthi; L., Arun (Tropical Journal of Pathology and Microbiology, 2019)
Introduction: Prostate cancer is the second most common cause of cancer and the sixth leading cause of cancer death among men worldwide, To diagnose prostate cancer, no specific single histologic feature is sufficiently available. It is a challenging task to accurately diagnose small foci of prostate cancer for pathologists and to distinguish cancer from its benign mimickers. Material and Methods: The present study was a prospective study. Establishing a definitive diagnosis of malignancy in prostate needle biopsies with very little foci of adenocarcinoma is a major diagnostic challenge for pathologists. A negative diagnostic marker specific for prostatic adenocarcinoma may enhance the ability to detect limited prostate cancer and reduce errors in diagnosis. The recent discovery of the 34βE12 in prostate cancer is a successful example of translating an advanced molecular finding into clinical practice. Results: Among 37 cases 19 were prostatic cancer, 5 were prostatic intraepithelial neoplasia, 1 case was atypical foci, and 9 were benign prostatic hyperplasia cases. 34βE12has been proven to be one of the few biomarkers that can help distinguish cancer from benign cells, with high sensitivity and specificity for prostate carcinoma. This study focuses on the study of 34βE12 expression in prostate cancer, premalignant lesions, benign prostate tissues, and other normal and malignant tissues and a discussion of its clinical usefulness. Conclusion: The present study recommends the interpretation of the 34βE12 immunohistochemical results in routine surgical pathology practice and also discuss the potential future applications of this marker in diagnosis of various lesions.